Identification of physical interaction between trimethoprim and sulfamethoxazole by contact method kofler and crystallization reaction - Zaini, Erizal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Identification of solid state interaction between TMP and SMZ by hot contact method Kofler and crystallization reaction had been carried out. The results of hot contact method Kofler shown formation a new crystalline habit as long and thin needle shaped on contact zone (mixing zone) between Solid TMP and SMZ. It had a different melting point in compared to its single component. Crystallization reaction between two of supersaturated solution of component TMP and SMZ in methanol solvent also indicated the growth of crystal habit as similar as hot contact method Kofler. Solid state interaction between TMP and SMZ was confirmed by microscopic SEM, powder X-ray diffraction, and thermal DSC. Microscopic analysis by SEM showed significantly the change of habit and morphology of crystal as long and thin needle shaped. New powder X-ray diffraction (PXRD) interferences peaks were observed in addition to PXRD interference peaks of each component that proved formation of cocrystalline phase. Thermogram DSC indicated a new endothermic peak corresponding to melting point of a new cocrystalline phase at temperature 178,82 °C.Key words : trimethoprim, sulfamethoxazole, physical interaction, cocrystalline phase